Comparative Study on the Social Psychology of Designed and Un-designed University Campus - Anik, Mohammad Rakibul Islam; Zohora, Fatema Tuz; Basure, Ashefa Washema; Rahman, Iftekhar (South Asian Journal of Social Sciences and Humanities, 2025)
This comparative Study on the Social Psychology of Designed and Undesigned Campuses examines how a campus’s intentionally or unintentionally designed landscape components influence students’ psychological impacts, attendance and social interactions. It is conducted by a designed online questionnaire based on the components of landscape desirability and students’ mental health responses to that such as understanding, exploration, compatibility with the desire for participation, and depression and anxiety. The questionnaire was given to a total of 100 university students. The sampling method was random clustering based on public and private university categories. The data from the questionnaire was analyzed using statistical methods and comparison techniques. The ultimate goal is to compare and prioritize the desirability factors of the designed landscape on campuses, and the student’s attendance at the university which can assist universities in creating environments that promote positive student experiences, reduce mental health issues, and increase attendance and social involvement. This study can inform future campus development, enhancing the entire educational experience and promoting student achievement through well-designed spaces.